Flux dynamics of C-5 amino acid precursors in fed-batch cultures of Streptomyces clavuligerus during clavulanic acid biosynthesis - Luisa María Gómez-Gaona, Howard Ramírez-Malule, David Gómez-Ríos (Journal of Applied Pharmaceutical Science, 2024)
Clavulanic acid (CA) is a well-known β-lactamase inhibitor that is mainly obtained from submerged cultures of Streptomyces clavuligerus. Dynamic genome-scale in silico studies were performed to gain insights into the intracellular metabolic fluxes of C-5 precursors during the cultivation of wild-type S. clavuligerus in batch and fed-batch operation. A preliminary literature screening was conducted for media selection and determination of culture conditions for further cultivation in a 5-L bioreactor. Simulations provided insights into the metabolism of C-5 precursors in CA biosynthesis. In addition, carbon utilization for CA biosynthesis was assessed in terms of the ratio of total carbon used in CA biosynthesis to the total carbon influx in batch and feed media. Based on simulation results, we proposed a modification of the glycerol-sucrose-proline-glutamate medium for fed-batch cultivation to improve the carbon utilization for CA biosynthesis. The proposed fed-batch scenario achieved higher specific CA concentration at lower biomass production, indicating better carbon utilization for its synthesis. The dynamic in silico fluxes suggests that metabolic fluxes in this scenario would be stable, favoring a longer stage of continued antibiotic secretion.
Keywords: Streptomyces, clavulanic acid, amino acids, dFBA, fed-batch